HOTEL SPA INTERNASIONAL DI BALI DENGAN PENDEKATAN ARSITEKTUR REGIONALISME - Shabrina Adani; Widi Suroto; Ofita Purwani (ARSITEKTURA, 2016)
Designing International Hotel & Spa in Bali is motivated by the growing number of domestic and foreign tourists visit in the field of tourism and business, the increasing number of distribution of tourist attraction in Bali, and the efforts to preserve Balinese spa as the cultural activity. There are modern and traditional elements of human needs at the background, so the purpose of this scheme is to offer traditional spa function on an international standard hotel in order to support tourism in Bali with a building design that shows smelting architecture of the present and the past through regionalism architecture. The issue is: how to design a commercial building that is multifunctional hotel and spa in Bali that have international standards using the approach of regionalism architecture as a design methodology. The result is the application of architectural regionalism Bali concretely in the form of buildings, building appearance and layout of the hotel building and spa.Keywords: Hotel, Regionalism Architecture of Bali, Spa